3D QSAR Analysis of 6-Isoxazolinyl and Isoxazolidinyl Substituted Quinazolinones as Angiotensin-II Receptor Antagonists - Banchhor, Madhuri; Chaturvedi, S.C. (Asian Journal of Chemistry, 2010)
Semi-emperical AM1 calculation was performed on 6-isoxazolinyl and isoxazolidinyl substituted quinazolinones as A-II receptor antagonists. The best QSAR equation obtained from 19 analogs of training set molecules revealed statically significant equation with following stastics; coefficient of determination (r2) = 0.645525, cross validated value (q2) = 0.894626, standard error of estimate (s) = 0.117655, fisher's F-value = 3.434560. Further, robustness and predictivity of the model was assessed externally by r2 predicted value (0.114659). This analysis revealed that steric, thermodynamic and electronic interactions are responsible for A-II receptor antagonistic activity. Based on QSAR results new analogues were designed and their IC50 values were determined theoretically.